2015
DOI: 10.1021/acsami.5b02783
|View full text |Cite
|
Sign up to set email alerts
|

Crystal-Orientation-Modulated Exchange Bias in Orthorhombic-YMnO3/La0.6Sr0.4MnO3 Multiferroic Heterostructures

Abstract: The magnetic properties of the all-oxide multiferroic heterostructures composed of orthorhombic YMnO3 (YMO) with E-type antiferromagnetic and double-exchange ferromagnetic (FM) La0.6Sr0.4MnO3 (LSMO) were studied. An orientation-modulated exchange bias effect, which is related to the interfacial Mn-O-Mn bond angle, was discovered. Because of the large bond angle in YMO/LSMO(100) heterostructures, a strong exchange coupling at the interface is formed. This strong exchange coupling sustains an FM phase in YMO at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…Our previous study on the magnetic properties of the YMO/LSMO/STO heterostructures with different lattice orientations showed that EB strongly depends on the lattice orientations with different Mn 3+ –O 2− –Mn 4+ bond angles at the interface 19 . Herewith, after the field cooling from 350 to 5 K with an in-plane magnetic field of 1 T, the hysteresis loops were measured.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Our previous study on the magnetic properties of the YMO/LSMO/STO heterostructures with different lattice orientations showed that EB strongly depends on the lattice orientations with different Mn 3+ –O 2− –Mn 4+ bond angles at the interface 19 . Herewith, after the field cooling from 350 to 5 K with an in-plane magnetic field of 1 T, the hysteresis loops were measured.…”
Section: Resultsmentioning
confidence: 98%
“…S3 ) 23 24 . The lattice-orientation dependent EB can be attributed to the difference of the interfacial Mn 3+ –O 2− –Mn 4+ bond angle which leads to the different strength of interfacial coupling in the heterostructures 19 . As a comparison, the temperature dependent EB of the LSMO/YMO/STO heterostructures is also shown in the inset of Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Charge freedom of oxide heterointerfaces plays an important role in strongly correlated oxide heterostructures . Generally, the valence states of interfacial ions can be effectively modified by charge transfer or doping . Modifying the valence of 3d ions can significantly affect the interfacial electronic structure, particularly the occupation of the 3d‐shell levels .…”
Section: Introductionmentioning
confidence: 99%
“…An enhanced coercivity and asymmetric shift in the magnetic hysteresis loop are the manifestations of EB in magnetic materials. Till date, most of the EB related applicative research is focussed to different FM-AF multilayered systems only456. However, implementation of EB in nanoparticles (NPs) instead of hundreds of ‘nm’ thick multi-layers can provide the magnetic devices much higher order of compactness.…”
mentioning
confidence: 99%